Analysis of sample rejection at newly established pathology laboratory of the International Islamic University Malaysia Medical Centre (IIUMMC) - Abdullah, Nor Zamzila; Muhammad, Siti Aeshah @ Naznin; Santosa, Rahajoe Imam; A.Talib, Norlelawati; Hamdan, Asmah Hanim; Mohd Sahir, Anirawati; Sazali, Mohd Zikri; Wan Ahmad, Wan Amirul Afiq; Asri, Nuralisa; Mohamad Rashid, Nor Khalidah (2017)
Introduction: Erroneous laboratory results due to pre-analytical errors may significantly affect patient’s safety and care. In diagnostic laboratory practice, stringent rejection criteria are therefore necessary. On the other hand, sample rejection may delay the turnaround time and decision for patient care. Inexperience staff combined with unfamiliarity with new hospital setting may contribute to escalate the pre-analytical errors. This is one of the challenges faced by our new hospital. Objective: The aim of this study was to determine the rate, type, cause and time of sample rejections at our laboratory since its operation in October 2016. Material & Methods: All samples received at the common specimen receiving counter, Department of Pathology and Laboratory Medicine, IIUMMC were included. The records of sample rejection were retrieved from the Laboratory Information System and analysed. Results: A total number of 1419 samples were received from October 2016 to March 2017, with 54 rejections (3.8%). The rate of sample rejection showed an upward trend each month (0%, 0%, 2.4%, 2.6%, 3.6% and 5.18% respectively from October 2016 to March 2017). Chemistry profiles and coagulation studies were among the commonest types of samples rejected (37% and 22.2% of the rejected samples respectively). Haemolysed sample was found to be the commonest cause of rejection (44.4%), followed by insufficient samples (35.2%). Most of the samples were rejected during morning working hours from 8.00am – 1.00pm (61.1%). Conclusion: The increasing rejection rate in our newly established Pathology laboratory warrants further investigation and improvement on proper sample collection and handling.